Fundamentals of Business - Skripak, Stephen J.; Parsons, Richard; Cortes, Anastasia (Open textbook library., 2018)
An introductory textbook in business that covers a variety of topics: The Foundations of Business, Economics and Business, Ethics and Social Responsibility, Business in a Global Environment, Forms of Business Ownership, Entrepreneurship: Starting a Business, Management and Leadership, Structuring Organizations, Operations Management, Motivating Employees, Managing Human Resources, Union/Management Issues, Marketing: Providing Value, Accounting and Financial Information, and Personal Finances.